Zoonotic metacestodes and associated financial loss from cattle slaughtered at Yabello municipal abattoir, Borana-Oromia, Ethiopia - Beyene, Tariku (Parasite Epidemiol Control, 2019)
Cross-sectional study was carried out to determine the prevalence and estimate financial losses associated with zoonotic metacestodes in cattle originated from Borana Pastoral Farming System and slaughtered at Yabello Municipal Abattoir, Ethiopia. A total of 384 cattle were randomly selected at the abattoir. Detailed postmortem examination, cyst count and fertile test were conducted. Significantly higher prevalence of Cystic echinococcosis (CE) (33.3%) with 5.3 times (OR 95% 3.5–8.1) than Cysticercus bovis (8.6%) was observed. Significant difference (p < 0.05) in prevalence of both CE and C. bovis were observed among the animal body condition, but not in other factors of the study. From total examined animals, 32.8%, 8.1% and 0.5% were infected by CE only, C. bovis only and both as concurrent infections, respectively. Significantly higher CE (p < 0.05) than C. bovis were observed within studied categories of risk factors. Tissue level cyst prevalence of 83.1% CE and 26.6% C. bovis were observed. High CE counts on the lungs (42.7%), liver (32.8%) and kidney (5.2%) but high C. bovis count in triceps muscle and masseter muscles (7.3% each) and heart (3.64%) were observed. Concurrent infections were observed in heart and liver. Out of the 347 counted CE cysts, fertile and viable were 34.0% and 23.1%, respectively. Of the counted C. bovis, 30.4% were both fertile and viable. A total of 301,139.6ETB (11,155.52USD) annual financial losses were calculated during the study period. The Borana Pastoral Farming System characterized by seasonal animal movement needs awareness creation on the elders and leaders regarding parasitic epidemiology and control strategies.